2020
DOI: 10.1080/20421338.2020.1835177
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing attitudes and intention to adopt financial technology services among the end-users in Lagos State, Nigeria

Abstract: Financial technology (Fintech) innovation has brought a dynamic change to the financial sector as new products and services are offered by conventional banks and other companies offering banking services through various online platforms. The attitudes of the end-users tend to play a great role in the adoption of any technology. This paper investigated the factors influencing the attitudes and intention of the end-users towards using Fintech services within the purview of an expanded technology acceptance model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 30 publications
4
10
0
1
Order By: Relevance
“…We use the convenience sampling technique prescribed by Cochran (2007) to determine that the final sample size for this study is 300. A similar technique has been adopted in recent studies on mobile banking adoption (Akinwale & Kyari, 2020;Talom & Tengeh, 2020) due to difficulties in determining a sampling frame.…”
Section: Methodsmentioning
confidence: 99%
“…We use the convenience sampling technique prescribed by Cochran (2007) to determine that the final sample size for this study is 300. A similar technique has been adopted in recent studies on mobile banking adoption (Akinwale & Kyari, 2020;Talom & Tengeh, 2020) due to difficulties in determining a sampling frame.…”
Section: Methodsmentioning
confidence: 99%
“…This research has analytical and statistical or quantitative inferences (Polit & Beck, 2010; Nasir et al, 2022; Zakari et al 2022). The current study has used innovation attributes of DOI theory by adding additional constructs and modifying relative advantage attributes (reflective formative higher‐order abstraction) to study determinants of non‐residential RSPV system adoption in the Indian context (Dagar et al, 2019; Mansour et al, 2020). The research framework of the current study can be replicated worldwide in the same form or a modified version to study RSPV system adoption (Alvarado et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on the drivers and motivations of solar energy diffusion and adoption highlighted the various factors influencing solar photovoltaic (SPV) system adoption. These factors comprise environmental concerns (Fathimah et al, 2020; Ghosh et al, 2020; Parsad et al, 2020; Qureshi et al, 2017; Reindl & Palm, 2021; Schelly & Letzelter, 2020), subsidies (Ghosh et al, 2020; Sun & Spicer, 2016), shielding from high electricity tariffs (Fathimah et al, 2020; Kiprop et al, 2019; Reindl & Palm, 2021), policy support (Ghosh et al, 2020; Pandey et al, 2012; Vasseur & Kemp, 2015), the honesty of sales representatives of solar photovoltaics (Schelly & Letzelter, 2020), sustainable energy technology (Akinwale & Adepoju, 2019), product benefits and social norms (Aziz et al, 2017; Qureshi et al, 2017), knowledge of the technology and passion in the technology (Schelly, 2014), etc. Kumar Singh et al (2022) found that reducing operating costs is a significant driver for adopting commercial and industrial SPV systems.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, instruments from the original technology adoption literature have been used (Davis et al, 1989; Venkatesh et al, 2012). As required, we have included instruments from fintech adoption literature (e.g., Akinwale & Kyari, 2022). Table 2 summarizes the measurement instruments.…”
Section: Methodsmentioning
confidence: 99%